Evaluation of high-school health science careers program impact on student retention and careers. - Zavattieri L; D'Anna S; Maillet JO (Journal of Allied Health)
The purpose of this research was to longitudinally measure the impact of the University of Medicine and Dentistry of New Jersey-School of Health Related Professions high-school Health Science Careers program on student retention in health careers. Students (n = 1,218) who earned college credit in the program from 1996 to 2002 were surveyed. The response rate was 17% of the total and 21% of the deliverable surveys. Students were equally distributed between vocational, comprehensive, and academy-type schools. Ninety-seven percent of the students continued their education after high school, with 70% attending 4-year colleges. Forty-nine percent of those entering 2-year colleges and 57% of those entering 4-year colleges pursued health-related careers. Ninety-five percent perceived the Health Science Careers program as valuable. The findings suggest that the Health Science Careers program was helpful in guiding students toward health-related professions. The evaluation helped to understand the impact and to realize the positive and negative aspects of the program by the respondents.